Recurring emergency general surgery: Characterizing a vulnerable population. Issue 3 (March 2019) - Lunardi, Nicole; Mehta, Ambar; Ezzeddine, Hiba; Canner, Joseph K.; Hamidi, Mohammad; Jehan, Faisal; Joseph, Bellal A.; Nathens, Avery B.; Efron, David T.; Diaz, Jose; Sakran, Joseph V.
Abstract : BACKGROUND: Limited data exist for long-term outcomes after emergency general surgeries (EGSs) in the United States. This study aimed to characterize the incidence of inpatient readmissions and additional operations within 6 months of an EGS procedure. METHODS: In this retrospective observational study, we identified adults (≥18 years old) undergoing one of seven common EGS procedures (appendectomies, cholecystectomies, small bowel resections, large bowel resections, control of gastrointestinal [GI] ulcers and bleeding, peritoneal adhesiolysis, and exploratory laparotomies) who were discharged alive in the 2010–2015 National Readmissions Database. Outcomes included the rates of all-cause inpatient readmissions and of undergoing a second EGS procedure, both within 6 months. Multivariable logistic regression models identified risk factors of reoperation, adjusting for patient, clinical, and hospital factors. RESULTS: Of 706, 678 patients undergoing an EGS procedure 131, 291 (18.6%) had an inpatient readmission within 6 months. Among those readmitted, 15, 178 (11.6%) underwent a second EGS procedure, occurring at a median of 45 days (interquartile range, 15–95). After adjustment, notable predictors of reoperation included male sex (adjusted odds ratio [aOR], 1.06 [95% confidence interval, 1.01–1.10]); private, nonprofit hospitals (aOR, 1.09 [1.02–1.17]); private, investor-owned hospitals (aOR, 1.09 [1.00–1.85]); discharge to short-term hospital (aOR, 1.35 [1.04–1.74]); discharge with home health care (aOR, 1.19 [1.13–1.25]); and index procedure of control of GI ulcer and bleeding (aOR, 9.38 [8.75–10.05]), laparotomy (aOR, 7.62 [6.92–8.40]), or large bowel resection (aOR, 6.94 [6.44–7.47]). CONCLUSION: One fifth of patients undergoing an EGS procedure had an inpatient readmission within 6 months, where one in nine of those underwent a second EGS procedure. As half of all second EGS procedures occurred within 6 weeks of the index procedure, identifying patients with the highest health care needs (index procedure type and discharge needs) may identify patients at risk for subsequent reoperation in nonemergency settings. LEVEL OF EVIDENCE: Epidemiological, level III. Abstract : Supplemental digital content is available in the text.